Analysis of Employee Performance Determinants: The Role of Work Life Balance, Work Family Conflict, and Work Motivation - Fatmasari Endayani; Ernita Dian Puspasari; Saman Saman (International Journal Business, Management and Innovation Review, 2025)
This study analyzes the determinants of employee performance through an investigation of the influence of work life balance, work family conflict, and work motivation in contemporary organizational contexts. A quantitative approach with a descriptive-verifiable design was applied to 100 permanent employee respondents who were selected using purposive sampling techniques. The research instrument in the form of a structured questionnaire with a five-point Likert scale has passed an adequate validity and reliability test. Data analysis used multiple linear regression techniques with the help of SPSS to test the research hypothesis. The results of the analysis showed that work motivation had a significant positive effect on employee performance (β=0.629; p<0.001), while work life balance showed a positive but insignificant effect (β=0.198; p=0.056), and work family conflict showed a negative influence that was not significant (β=-0.012; p=0.888). Simultaneously, the three independent variables explained 55.7% of the variance in employee performance (Adjusted R²=0.557). The findings confirm the dominance of motivational factors in shaping optimal employee performance. The practical implications emphasize the need for organizations to develop strategies to increase work motivation through a comprehensive reward system and the creation of a conducive work environment to support the achievement of sustainable performance.